STRATEGI DAKWAH GUS YUSUF CHUDLORI MELALUI MEDIA SOSIAL - Faradhita Novitrianti; Moh. Yasir Alimi (Jurnal Ilmiah Sosiologi Agama (JISA), 2026)
The development of social media has transformed Islamic preaching practices from one-way communication into a dialogical space involving negotiation of religious authority and audience participation. This study aims to analyze the digital preaching model based on the pesantren tradition developed by Gus Yusuf Chudlori on social media and its implications for the construction of religious authority and the audience's understanding of religiosity. This study uses a qualitative approach with thematic content analysis of preaching posts on YouTube and Instagram @gusyusufchannel for the period January–June 2025, complemented by in-depth interviews with the account manager. The research results show that Gus Yusuf's preaching represents a form of negotiation between traditional pesantren religious authority and the logic of social media, characterized by the use of classical book references, communicative language, a moderate approach, and optimization of platform features to build audience engagement. This finding indicates that digital da'wah based on pesantren does not experience a degradation of authority, but rather undergoes a transformation through the adaptive practice of mediatization of religion. This study contributes to the development of digital da'wah and religious communication studies in the new media era.